(untitled) (Proceedings of Faculty of Civil Engineering, 2022)
A hydrological-hydraulic analysis of a sustainable storm water drainage system in the city of Šibenik, the Dalmare commercial zone, was carried out in this study. The main aim is to assess how the blue-green infrastructure (BGI) positively affects the stormwater drainage system and environment. The results of the analyses indicate a significant reduction in the peak flow and volume of stormwater runoff after the implementation of BGI, as well as an improvement in the stormwater quality.